Lipoxin A4 Reduces Ventilator-Induced Lung Injury in Rats with Large-Volume Mechanical Ventilation - Qi Wang; Guang-xiao Xu; Qi-hang Tai; Yan Wang (Mediators of Inflammation)
Ventilator-induced lung injury (VILI) is a severe and inevitable complication in patients who require mechanical ventilation (MV) for respiratory support. Lipoxin A4 is an endogenous anti-inflammatory and antioxidant mediator. The present study determined the effects of lipoxin A4 on VILI. Twenty-four rats were randomized to the sham, VILI, and lipoxin A4 (LX4) groups. The rats in the VILI and LX4 groups received large-volume MV for 4 hours to simulate VILI. Capillary permeability was evaluated using the PaO2/FiO2 ratio, lung wet/dry weight ratio, and protein level in the lung. VILI-induced inflammation was assessed by measuring cytokines in serum and lung tissue, the expression and activity of NF-κB, and phosphorylated myosin light chain. The oxidative stress response, lung tissue injury, and apoptosis in lung tissue were also estimated, and the expression of apoptotic proteins was examined. MV worsened all of the indices compared to the sham group. Compared to the VILI group, the LX4 group showed significantly improved alveolar-capillary permeability (increased PaO2/FiO2 and decreased wet/dry weight ratios and protein levels), ameliorated histological injury, and reduced local and systemic inflammation (downregulated proinflammatory factors and NF-κB expression and activity). Lipoxin A4 notably inhibited the oxidative stress response and apoptosis and balanced apoptotic protein levels in lung tissue. Lipoxin A4 protects against VILI via anti-inflammatory, antioxidant, and antiapoptotic effects.